Effectiveness and safety of direct oral anticoagulants versus vitamin K antagonists in atrial fibrillation patients with liver disease: a systematic review and meta-analysis - Zhou, Qiang; Liu, Xiang; Liu, Shuyu; Gu, Zhichun; Wu, Yanzi; Yang, Yuansu; Tao, Yingying; Wei, Meng (Frontiers in Pharmacology, 2025)
IntroductionPatients with atrial fibrillation (AF) and liver disease, particularly cirrhosis, are frequently excluded from anticoagulation trials, leaving the optimal therapeutic strategy uncertain.MethodsThis study aimed to compare the effectiveness and safety of direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) in patients with AF and liver disease. We systematically searched the PubMed, Cochrane Library, Medline, and Embase databases for relevant studies published up to November 2024.ResultsFourteen studies, involving 44,848 participants, were included. Compared to VKAs, DOACs were associated with significantly lower risks of major bleeding (risk ratio [RR]: 0.64, 95% confidence interval [CI]: 0.55–0.75; P < 0.0001), intracranial bleeding (RR: 0.43, 95% CI: 0.33–0.56; P < 0.0001), gastrointestinal (GI) bleeding (RR: 0.72, 95% CI: 0.59–0.89; P = 0.002), and all-cause mortality (RR: 0.83, 95% CI: 0.70–0.98; P = 0.03). No significant difference was observed in ischemic stroke/systemic embolism (RR: 0.77, 95% CI: 0.52–1.13; P = 0.19). In patients with cirrhosis, DOACs were similarly superior for major bleeding, GI bleeding, and intracranial bleeding. Subgroup analyses revealed that apixaban demonstrated a more favorable safety profile than rivaroxaban in patients with liver disease, whereas both agents showed comparable effectiveness and safety in cirrhotic patients.ConclusionDOACs are safer and equally effective alternatives to VKAs in patients with AF and liver disease, including those with cirrhosis. In patients with liver disease, apixaban may offer additional safety benefits compared with rivaroxaban. However, in patients with cirrhosis, the effectiveness and safety profiles of the two drugs are similar.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024623387